6 Let's stick together: What are the relationship needs of caregivers of people with dementia at the end of life?. (14th March 2023) - Lewis, Juliette; Harris, Dylan
Abstract : Background: Globally, the incidence and prevalence of dementia are increasing exponentially. Caregiving is a clinically and socially relevant issue to dementia care. Informal care provision is a strong determinant of social and health inequalities throughout the life course (European Centre for Social Welfare Policy and Research 2021). Therefore, understanding the needs of caregivers is essential in terms of improving future dementia care worldwide. Methods: A systematic review was conducted using the PRISMA framework and a narrative synthesis was performed. The electronic databases searched were APA PsycINFO, Ovid AMED, CINAHL by EBSCO, Cochrane Database, Ovid EMBASE, Ovid EMCARE and Ovid MEDLINE. Inclusion criteria: English-language studies. Population: adults aged >18 years identified as informal caregivers of a formally-diagnosed person with dementia (PWD). Phenomenon of interest: psychological needs. Context: end of life (EOL) period of PWD. Results: Caregivers identified three key relationship needs whilst caregiving for a PWD at EOL: i) the need for connection and intimacy at the EOL (including opportunities for forgiveness and rebuilding relationships); ii) the need to find joy and positivity and iii) the need to say goodbye. Additionally, many caregivers reported the benefits of sharing experiences with other caregivers; it fostered a sense of solidarity, normalised the experience and offered validation from peers. Caregivers found emotional security in setting boundaries, building relationships with staff and having confidence in staff expertise. The need for caregivers to feel a sense of control during the EOL period was also identified. Role recognition in the form of both acknowledgement of caregiving duties and defining an identity outside the caregiving role were fundamental relationship needs. Conclusion: Caregivers wanted to feel listened to, primarily as advocates for PWD but also to validate their caregiving role and recognise the intimate knowledge that they have acquired whilst caregiving for a PWD at EOL.